Systematic Analysis of Literature on the Marketing of Healthcare Systems. Challenges for Russian and Romanian Healthcare Systems - Bulatnikov, Vladimir; Constantin, Cristinel Petrişor (MDPI AG, 2021)
This paper aims at finding the most dominant ideas about the marketing of healthcare systems highlighted in the mainstream literature, with a focus on Russia and Romania. To reach this goal, a systematic analysis of literature was conducted and various competitive advantages and disadvantages of the medical models that require special attention from the governments are considered. In this respect we examined 106 papers published during 2006 to 2020 found on four scientific databases. They were selected using inclusion and exclusion criteria according to PRISMA methodology. The main findings of the research consist of the opportunity to use marketing tools in order to improve the quality of healthcare systems in the named countries. Thus, using market orientation, the managers of healthcare systems could stimulate the innovation, the efficiency of funds allocation and the quality of medical services. The results will lead to a better quality of population life and to an increasing of life expectancy. As this paper reviews some articles from Russian literature, it can add a new perspective to the topic. These outcomes have implications for government, business environment, and academia, which should cooperate in order to develop the healthcare system using marketing strategies.